Contaminated Pond Water Favors Cholera Outbreak at Haibatpur Village, Purba Medinipur District, West Bengal, India - Dilip Kumar Biswas; Rama Bhunia; Dipankar Maji; Palash Das (Journal of Tropical Medicine)
Health workers reported an increased number of diarrhea cases at Haibatpur village on June 17, 2012. This outbreak was investigated with the following objectives: to confirm the existence of diarrhea outbreak, to find out the risk factors, and propose control measures. Cases were listed; spot map and epidemic curve were drawn. Attack rate was calculated by age and sex and risk factors were found out by calculating odds ratio (OR) with 95% confidence interval (CI). Rectal swabs were taken and water specimens were collected for laboratory test. Forty-one cases of patients were identified with overall attack rate (AR) was 5% (41/780). AR among men was higher 6% (25/404) than women. There was no death. V. cholerae 01 Eltor Ogawa was isolated from one (1/4) stool specimen. Spot map showed cases clustered around two ponds which were contaminated with coliform organisms. The underground water was a bit saline in nature. Using pond water for preparation of fermented rice (Panta Bhat) (OR 4.73, 95% CI 1.69–13.51), washing utensil in pond water (OR 7.31, 95% CI 1.77–42.29) were associated with cholera outbreak. Health education was done to villagers. Disinfection of two ponds with bleaching powder was done. We proposed supplying of safe drinking water and repairing defective deep tube well to village.